2004
DOI: 10.1111/j.1443-9573.2004.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sensitivities of distinct gastric cancer cells to parvovirus H‐1 induced cytotoxicity

Abstract: The sensitivities of the distinct gastric cancer cells to H-1 virus induced cytotoxicity were markedly different. In general, the poorly differentiated cells showed an enhanced sensitivity to H-1 virus attack compared with well-differentiated ones. The enhanced sensitivity of poorly versus well-differentiated gastric cancer cells to H-1 virus is related in part to the enhanced capacity of the former for NS1 protein production and accumulation. The undifferentiated BGC823 cells were resistant to H-1 virus trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
2
5
0
Order By: Relevance
“…In contrast, the NS1 transduction of MKN28 cells was not associated with a significant decrease of their tumorigenicity, as compared to parental or empty vector‐transfected controls. A parallel can be drawn between these results and our previous study showing that MKN28 cells can be distinguished from MKN45 and SGC7901 cells by their much lower sensitivity to the toxic activity of parvovirus H‐1 12 …”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In contrast, the NS1 transduction of MKN28 cells was not associated with a significant decrease of their tumorigenicity, as compared to parental or empty vector‐transfected controls. A parallel can be drawn between these results and our previous study showing that MKN28 cells can be distinguished from MKN45 and SGC7901 cells by their much lower sensitivity to the toxic activity of parvovirus H‐1 12 …”
Section: Discussionsupporting
confidence: 83%
“…In contrast, no difference in growth rate was found in the MKN28‐derived transfectants. These data may be correlated with the insensitivity of the parental cell line to infection with parvovirus H‐1 described previously 12 . In addition, NS1 expression in MKN45 and SGC7901 cells correlated with a striking suppression of their capacity to form tumors after xenografting into immunodeficient mice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Although we observed that KLK12 had a similar effect on cell proliferation and migration in all three cell lines, AGS cells displayed a lower degree of differentiation in the S phase (Ran et al, 2004). This is of relevance considering that Helicobacter pylori can easily adhere to and invade human gastric epithelial cells.…”
Section: Discussionmentioning
confidence: 59%
“…For example, SGC‐7901 (moderately differentiated) and MKN‐28 (well differentiated) are two distinctly differentiated gastric cancer cell lines and they could respond differently upon the exposure to anticancer compounds. It has been shown that six gastric cancer cell lines had different sensitivities for the cytotoxic effects of parvovirus H‐1 (Ran et al . 2004).…”
Section: Resultsmentioning
confidence: 99%